(untitled) (Terr@ Plural, 2024)
The stratigraphic framework in the southern portion of the Paraná Basin, represented by the Devonian System strata, preserves a rich fossil deposit. This deposit is marked by the presence of a paleofauna commonly referred to as endemic, composed of benthic organisms from the Malvinocaffric Realm. The present study constitutes the interpretation of a new depositional section, and for this purpose, the new areas were visited in the field and described in terms of facies, ichnology, and taphonomy. The research resulted in the interpretation of facies from a marine environment influenced by storms in a situation of ecological stress established immediately before the Kačák extinction event.